CARBON STOCKS, LITTERFALL AND PRUNING RESIDUES IN MONOCULTURE AND AGROFORESTRY CACAO PRODUCTION SYSTEMS. (6th May 2018) - SCHNEIDEWIND, ULF; NIETHER, WIEBKE; ARMENGOT, LAURA; SCHNEIDER, MONIKA; SAUER, DANIELA; HEITKAMP, FELIX; GEROLD, GERHARD
SUMMARY: Agroforestry systems (AFS) can serve to decrease ecosystem carbon (C) losses caused by deforestation and inadequate soil management. Because of their shade tolerance, cacao plants are suitable to be grown in AFS, since they can be combined with other kinds of trees and shrubs. The potential for C sequestration in cacao farming systems depends on various factors, such as management practices, stand structure and plantation age. We compared conventionally and organically managed cacao monoculture systems (MCS) and AFS in Sara Ana (Bolivia) with respect to C stocks in plant biomass and to amounts of litterfall and pruning residues. The total aboveground C stocks of the AFS (26 Mg C ha −1 ) considerably exceeded those of the MCS (~7 Mg C ha −1 ), although the biomass of cacao trees was greater in the MCS compared to the AFS. Due to higher tree density, annual litterfall in the AFS (2.2 Mg C ha −1 year −1 ) substantially exceeded that in the MCS (1.2 Mg C ha −1 year −1 ). The amounts of C in pruning residues (2.6 Mg C ha −1 year −1 in MCS to 4.3 Mg C ha −1 year −1 in AFS) was more than twice those in the litterfall. Annual nitrogen (N) inputs to the soil through pruning residues of cacao and N-fixing trees were up to 10 times higher than the N inputs through external fertiliser application. We conclude that appropriate management of cacao AFS, involving the pruning of leguminous trees, will lead to increases in biomass, litter quantity and quality as well as soil C and N stocks. Thus, we recommend stimulating the expansion of well-managed AFS to improve soil fertility and enhance C sequestration in soils.